Cztery fale ewangelizacji. Refleksja o. Raniera kard. Cantalamessy na temat głoszenia kerygmatu w historii Kościoła - Zborowski, Michał (Annales Missiologici Posnanienses, 2023)
Father Raniero Cardinal Cantalamessa presents four periods of evangelization that have taken place in the history of the Church. He refers to them as „waves of evangelization”, indicating that these extraordinary periods of evangelization are reminiscences of the beginnings of the Church. Their appearance is related to the emergence of a new group of recipients unfamiliar with the message of the Gospel. Cantalamessa’s analysis indicates that the actual content conveyed to them is the kerygma. Appropriate pastoral reflection is also required by the choice of a keryx who is to effectively reach the recipients with the message of salvation. The four „waves of evangelization” are, according to the Italian theologian, a return to kerygmatic evangelization.